BRACED BIPOD PLATFORM FOR MARGINAL FIELD ALTERNATIVE - Ramadhani, Luthfi
Marginal field is relevant topic in current oil and gas industry. It becomes an engineering challenge to find at least one economic solution. This thesis introduces a new type of offshore platform, named “Braced Bipod Platform”, as an alternative solution for minimum offshore platform in water depth of up to 100 m.